2017
DOI: 10.1186/s12915-017-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of strigolactone receptors by gradual neo-functionalization of KAI2 paralogues

Abstract: BackgroundStrigolactones (SLs) are a class of plant hormones that control many aspects of plant growth. The SL signalling mechanism is homologous to that of karrikins (KARs), smoke-derived compounds that stimulate seed germination. In angiosperms, the SL receptor is an α/β-hydrolase known as DWARF14 (D14); its close homologue, KARRIKIN INSENSITIVE2 (KAI2), functions as a KAR receptor and likely recognizes an uncharacterized, endogenous signal (‘KL’). Previous phylogenetic analyses have suggested that the KAI2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 69 publications
7
143
0
1
Order By: Relevance
“…Phylogenetic analysis of full‐length predicted MAX2 proteins indicated that, in contrast to previously published phylogenies that used a higher number of expressed sequence tags and full‐length sequences, MAX2 from P. patens , Marchantia polymorpha and Selaginella moellendorffii formed a separate clade to seed plant proteins (Fig. S3a) (Delaux et al ., ; Bythell‐Douglas et al ., ). Thus, the precise relationships between MAX2 homologues in vascular plants and those in nonvascular plants remain ambiguous.…”
Section: Resultsmentioning
confidence: 97%
“…Phylogenetic analysis of full‐length predicted MAX2 proteins indicated that, in contrast to previously published phylogenies that used a higher number of expressed sequence tags and full‐length sequences, MAX2 from P. patens , Marchantia polymorpha and Selaginella moellendorffii formed a separate clade to seed plant proteins (Fig. S3a) (Delaux et al ., ; Bythell‐Douglas et al ., ). Thus, the precise relationships between MAX2 homologues in vascular plants and those in nonvascular plants remain ambiguous.…”
Section: Resultsmentioning
confidence: 97%
“…In this second pathway MAX2 is thought to interact with KAI2 (KARRIKIN-INSENSITIVE2), a receptor protein of the α/ hydrolase family, which is encoded by an evolutionary older paralog of D14 (Delaux et al, 2012;Toh et al, 2014;Bythell-Douglas et al, 2017). KAI2 was first identified as a receptor for karrikins, a family of butenolide compounds found in the smoke of burnt plant material (Waters et al, 2012b;Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some non‐conserved amino acids were also found to mediate the unique ligand binding profile of KAI2iB in S. hermonthica and the exertion of evolutionary forces on these residues possibly led to the diversification of KAI2 receptors (Xu et al ). Bythell‐Douglas et al () phylogenetically analyzed 339 members of the D14/KAI2 family from land plants and charophyte algae. The study suggested that SL perception actually evolved via neo‐functionalization of the D14/KAI2 family, and the transition from KAI2‐like to D14‐like proteins was induced by protein interactions rather than by the requirement of SL perception (Bythell‐Douglas et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Bythell‐Douglas et al () phylogenetically analyzed 339 members of the D14/KAI2 family from land plants and charophyte algae. The study suggested that SL perception actually evolved via neo‐functionalization of the D14/KAI2 family, and the transition from KAI2‐like to D14‐like proteins was induced by protein interactions rather than by the requirement of SL perception (Bythell‐Douglas et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation